Daños causados por cancro cítrico en la producción de naranja dulce 'Valencia' - Brugnara, Eduardo Cesar; Theodoro, Gustavo de Faria; Nesi, Cristiano Nunes; Verona, Luiz Augusto Ferreira; Maringoni, Antonio Carlos [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
The citrus canker, caused by Xanthomonas axonopodis pv. citri, is one of the main citrus diseases and has threatened the world's citriculture. In this study, the damage caused by citrus canker was quantified in a sweet orange culture, cv. Valencia [Citrus sinensis (L.) Osb.], grafted over 15 year-old Rangpur lime (C. limonia Osb.), in the municipality of Guatambu, SC, Brazil, in the crop of 2004/05. Evaluations of the number of fruits per plant (NF), fruit yield per plant (P), citrus canker incidence on the fruit (IFR), and incidence (IL) and severity (SV) of citrus canker on 80 leaves per orange tree were performed in the harvest period, applying diagrammatical scales. Plants had large variation in SV (0.16%-1.09%), IL (12.50%-56.25%) and IFR (12.30%-56.09%). Linear regressions were significant between IL x SV, NF x SV, P x IFR, and NF x IFR. There was no significant difference (p>0.05) between the mean estimated values of IL in different quadrants of the crowns of the orange trees (N, S, L and O). Each 1% increase in IFR reduced 2.16 kg and 21.3 fruits per tree.
Damage caused by citrus canker on valencia sweet orange yield
Keywords: Citrus sinensis; Incidence; Severity; Xanthomonas axonopodis pv. citri